Ultraviolet-attenuation-resistant film layer of solar cell, preparation method of ultraviolet-attenuation-resistant film layer and solar cell
By setting up a three-layer anti-ultraviolet attenuation film on the surface of the crystalline silicon of the solar cell, the problem that the anti-reflective layer cannot effectively absorb ultraviolet light is solved, the ultraviolet light absorption and passivation performance of the battery is improved, the battery life is extended and the battery efficiency is improved.
Patent Information
- Application Number
- CN202510678033.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-19
AI Technical Summary
The anti-reflection layer of existing solar cells cannot effectively absorb ultraviolet light, resulting in large optical reflection loss and poor passivation performance, which affects battery efficiency.
A three-layer structure anti-ultraviolet attenuation film layer is arranged on the surface of the crystalline silicon, including the upper silicon oxide, the middle silicon nitride-TiO2 composite layer, with the TiO2 doping ratio of 1% to 10%. It is formed by controlling the proportional deposition of gas flow, and the refractive index gradient is optimized to improve ultraviolet light absorption and passivation performance.
It significantly improves the ultraviolet light absorption capacity of solar cells, reduces damage to the passivation layer and silicon matrix by high-energy ultraviolet photons, reduces reflection loss, extends battery life and increases short-circuit current.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to an anti-ultraviolet attenuation film layer of a solar cell, a preparation method thereof, and a solar cell. Background Art
[0002] In high-efficiency solar cells (such as Topcon, PERC), the front side silicon nitride (SiN x ) The anti-reflection layer is not only used to reduce optical reflection loss, but also plays the role of surface passivation. However, the traditional SiN x The absorption capacity of the layer to ultraviolet light is limited, and high-energy ultraviolet photons may penetrate SiN x layer, resulting in defects at the interface between the passivation layer (such as SiO2) and the silicon substrate, causing battery performance degradation (such as UV-induced degradation, LeTID effect).
[0003] In the prior art, SiN is usually optimized x The thickness or refractive index of the layer can be used to improve the optical performance, but it is difficult to take into account both UV protection and passivation effects. x While optical performance can be improved by adjusting the thickness or refractive index of the layer, it is difficult to achieve both UV protection and passivation effects. For example, patent publication number CN119521856A provides a film structure for improving UV attenuation in TOPcon cells. A second silicon oxide layer and a first silicon oxide layer are respectively provided above and below the aluminum oxide layer, and a silicon nitride layer is provided on the surface of the second silicon oxide layer. This effectively reduces the attenuation rate of the cell and extends its service life. However, the two-layer silicon oxide structure will seriously hinder the transmission of carriers, reduce FF, and thus affect cell efficiency. At the same time, the blocking effect on UV penetration of the front passivation layer is not very obvious.
[0004] Therefore, an anti-reflection layer structure is urgently needed to improve the defects of traditional anti-reflection layers, such as inability to effectively absorb ultraviolet light, large optical reflection loss, and poor passivation performance. Summary of the Invention
[0005] Based on this, the purpose of the present invention is to provide an anti-ultraviolet attenuation film layer for solar cells and its preparation method, as well as a solar cell, which has solved the problems in the prior art that the anti-reflection layer cannot effectively absorb ultraviolet light, has large optical reflection losses, and has poor passivation performance.
[0006] To achieve the above-mentioned purpose, the present invention adopts the following technical solutions.
[0007] The present invention provides an anti-ultraviolet attenuation film layer for a solar cell, comprising: an anti-ultraviolet attenuation film layer with an upper, middle and lower three-layer structure provided on the upper surface of crystalline silicon; the upper layer is a silicon oxide layer; the middle layer is a silicon oxynitride layer; and the lower layer is a silicon nitride-TiO2 composite layer.
[0008] The present invention provides a film layer for solar cells that resists ultraviolet attenuation. The bottom layer of the film layer is doped with silicon nitride (SiN) x ), TiO2 has a band gap of approximately 3.0-3.2 eV (corresponding to an absorption wavelength of ≤400 nm), which can efficiently absorb ultraviolet light and reduce the penetration of high-energy photons into the battery, thereby reducing UV radiation damage to the passivation layer (such as SiO2 / polysilicon). It can effectively absorb ultraviolet light while maintaining excellent passivation and optical properties; reduce reflection loss in the 300-500 nm band, increase short-circuit current (Jsc) and significantly improve SiN x The ultraviolet absorption capacity of the layer can reduce the damage of high-energy ultraviolet photons to the passivation layer and the silicon substrate.
[0009] In some embodiments of the present invention, the silicon nitride-TiO2 composite layer includes: a stacked silicon nitride layer and a TiO2 layer, or a TiO2-doped silicon nitride layer.
[0010] In some embodiments of the present invention, stacking the silicon nitride layer and the TiO2 layer includes: stacking the TiO2 layer on the silicon nitride layer, or stacking the silicon nitride layer on the TiO2 layer.
[0011] In some embodiments of the present invention, the TiO2-doped silicon nitride layer has a TiO2-doped content of 1% to 10% by weight, specifically, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight.
[0012] In some embodiments of the present invention, when the silicon nitride layer and the TiO2 layer are superimposed, the thickness of the TiO2 layer is 5 nm to 20 nm. Specifically, the thickness of the TiO2 layer is 5 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, or 20 nm. The thickness of the silicon nitride layer is 45 nm to 115 nm. Specifically, the thickness of the silicon nitride layer is 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, or 115 nm.
[0013] In some embodiments of the present invention, the silicon nitride-TiO2 composite layer has a thickness of 50 nm to 120 nm. Specifically, the silicon nitride-TiO2 composite layer has a thickness of 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, or 120 nm.
[0014] In some embodiments of the present invention, the thickness of the upper layer is 8-15 nm.
[0015] In some embodiments of the present invention, the thickness of the middle layer is 15-25 nm.
[0016] The present invention also provides a method for preparing the anti-ultraviolet attenuation film layer of the solar cell, comprising:
[0017] S1, depositing a silicon nitride-TiO2 composite layer on the cell to be coated as the lower layer of the anti-ultraviolet attenuation film layer; depositing a silicon oxynitride layer on the lower layer as the middle layer of the anti-ultraviolet attenuation film layer of the solar cell; and depositing a silicon oxide layer on the middle layer as the upper layer of the anti-ultraviolet attenuation film layer of the solar cell;
[0018] S2, annealing the cell after the treatment in S1 to obtain the anti-ultraviolet attenuation film layer of the solar cell.
[0019] In some embodiments of the present invention, in S1, the thickness of the lower layer is 50 nm to 120 nm.
[0020] In some embodiments of the present invention, in S1, a silicon source, a nitrogen source, and a titanium source are introduced, and the ratio of the nitrogen source, the silicon source, and the titanium source is controlled to be 10:2:1 to deposit the lower layer.
[0021] In some embodiments of the present invention, the deposition temperature of the lower layer is 300° C. to 500° C., the pressure is 100 Pa to 500 Pa, the deposition time is 150 s to 300 s, and the discharge power is 9000 W to 15000 W.
[0022] In some embodiments of the present invention, S2, annealing conditions are: annealing temperature is 400° C. to 500° C., and time is 10 min to 20 min.
[0023] In some embodiments of the present invention, in S1, the cell to be coated is a passivated cell.
[0024] The present invention mainly dopes TiO2 into the lower layer of silicon nitride. The upper and middle layers are the same as the existing technology. The doping ratio of TiO2 in the bottom layer is 1%~10% (weight percentage). This ratio is controlled by the gas flow ratio. For example, if the ratio is NH3:SiH4:TiCl4=10:2:1, the doping ratio is about 5%. The doping ratio can be changed by appropriately increasing or decreasing the flow rate of TiCl4.
[0025] The present invention also provides a solar cell comprising the anti-ultraviolet attenuation film layer of the solar cell or comprising the film layer prepared by the preparation method.
[0026] Based on the technical solution of the present invention, compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. In the present invention, the band gap of TiO2 is about 3.0-3.2 eV (corresponding to absorption wavelength ≤ 400 nm), which can efficiently absorb ultraviolet light and reduce the penetration of high-energy photons into the battery, thereby reducing UV radiation damage to the passivation layer (such as SiO2 / polysilicon). By doping with TiO2, the SiN x The ultraviolet absorption capacity of the layer can reduce the damage of high-energy ultraviolet photons to the passivation layer and silicon substrate. x Deposition process, no major changes to production line equipment are required.
[0028] 2. The anti-ultraviolet attenuation film layer of the solar cell provided by the present invention has three layers of film, the upper, middle and lower layers, which gradually transition the refractive index of the incident light through a refractive index gradient from low to high (the refractive index close to the silicon substrate is high), thereby reducing reflection loss and improving the passivation performance of the overall film layer, thereby improving the performance of the battery.
[0029] 3. Optimize SiN x :The refractive index of the TiO2 composite layer is made closer to that of silicon, which reduces the reflection loss in the 300 nm~500 nm band and increases the short-circuit current (Jsc).
[0030] 4. Through the uniform distribution of nano-scale TiO2 particles, the mechanical strength and chemical stability of the composite layer are enhanced, thus extending the battery life. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0032] The following describes the details in conjunction with specific embodiments.
[0033] Example 1
[0034] A method for preparing a film layer resistant to ultraviolet attenuation of a solar cell, the method comprising:
[0035] 1. Place the passivated (passivation layer is an aluminum oxide layer with a thickness of 4nm) solar cells to be coated in a graphite boat;
[0036] 2. Place the graphite boat into the tubular coating reaction process furnace tube, heat and evacuate at the same time; the heating temperature is 400℃ and the vacuum degree is 200Pa;
[0037] 3. NH3, SiH4 and TiCl4 were introduced, and the gas flow ratio was controlled to be NH3:SiH4:TiCl4=50:10:1. The deposition temperature was 300℃, the pressure was 100Pa, the deposition time was 150s, and the discharge power was 9000W to form a bottom SiNx:TiO2 composite layer (the doping weight percentage of TiO2 was 1%). The film thickness was 50nm.
[0038] 4. SiH4, NH3 and N2O were introduced, and the gas flow ratio was controlled to be 1:5:7. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 200 s, and the discharge power was 12000 W to form a middle silicon oxynitride layer with a thickness of 20 nm.
[0039] 5. SiH4 and N2O were introduced, and the gas flow ratio was controlled to be 1:10. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 100 s, and the discharge power was 12000 W to form an upper silicon oxide layer with a thickness of 10 nm.
[0040] 6. Anneal the deposited silicon wafer at 400°C for 20 minutes to enhance the density and passivation effect of the composite layer.
[0041] 7. Back pressure, unloading from the boat to complete the process.
[0042] Example 2
[0043] A method for preparing a film layer resistant to ultraviolet attenuation of a solar cell, the method comprising:
[0044] 1. Place the passivated (passivation layer is an aluminum oxide layer with a thickness of 5nm) solar cells to be coated in a graphite boat;
[0045] 2. Place the graphite boat into the tubular coating reaction process furnace tube, heat and evacuate at the same time;
[0046] 3. NH3, SiH4 and TiCl4 were introduced, and the gas flow ratio was controlled to be NH3:SiH4:TiCl4=10:2:1. The deposition temperature was 300℃, the pressure was 100 Pa, the deposition time was 150s, and the discharge power was 9000W to form the bottom SiN x : TiO2 composite layer (TiO2 doping weight percentage is 5%), the film thickness is 50nm;
[0047] 4. SiH4, NH3 and N2O were introduced, and the gas flow ratio was controlled to be 1:5:7. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 200 s, and the discharge power was 12000 W to form a middle silicon oxynitride layer with a thickness of 20 nm.
[0048] 5. SiH4 and N2O were introduced, and the gas flow ratio was controlled to be 1:10. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 100 s, and the discharge power was 12000 W to form an upper silicon oxide layer with a thickness of 10 nm.
[0049] 6. Anneal the deposited silicon wafer at 400°C for 20 minutes to enhance the density and passivation effect of the composite layer.
[0050] 7. Back pressure, unloading from the boat to complete the process.
[0051] Example 3
[0052] A method for preparing a film layer resistant to ultraviolet attenuation of a solar cell, the method comprising:
[0053] 1. Place the passivated (passivation layer is an aluminum oxide layer with a thickness of 6nm) solar cells to be coated in a graphite boat;
[0054] 2. Place the graphite boat into the tubular coating reaction process furnace tube, heat and evacuate at the same time;
[0055] 3. NH3, SiH4 and TiCl4 were introduced, and the gas flow ratio was controlled to be NH3:SiH4:TiCl4=25:5:4. The deposition temperature was 400℃, the pressure was 300 Pa, the deposition time was 200s, and the discharge power was 11000W to form the bottom SiN x : TiO2 composite layer (TiO2 doping weight percentage is 8%), the film thickness is 80nm;
[0056] 4. SiH4, NH3 and N2O were introduced, and the gas flow ratio was controlled to be 1:5:7. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 200 s, and the discharge power was 12000 W to form a middle silicon oxynitride layer with a thickness of 20 nm.
[0057] 5. SiH4 and N2O were introduced, and the gas flow ratio was controlled to be 1:10. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 100 s, and the discharge power was 12000 W to form an upper silicon oxide layer with a thickness of 10 nm.
[0058] 6. Anneal the deposited silicon wafer at 450°C for 10 minutes to enhance the density and passivation effect of the composite layer.
[0059] 7. Back pressure, unloading from the boat to complete the process.
[0060] Example 4
[0061] A method for preparing a film layer resistant to ultraviolet attenuation of a solar cell, the method comprising:
[0062] 1. Place the passivated (passivation layer is an aluminum oxide layer with a thickness of 4nm) solar cells to be coated in a graphite boat;
[0063] 2. Place the graphite boat into the tubular coating reaction process furnace tube, heat and evacuate at the same time;
[0064] 3. NH3, SiH4 and TiCl4 were introduced, and the gas flow ratio was controlled to be NH3:SiH4:TiCl4=10:1:3. The deposition temperature was 500℃, the pressure was 500 Pa, the deposition time was 250s, and the discharge power was 12000W to form the bottom SiN x : TiO2 composite layer (TiO2 doping weight percentage is 15%), the film thickness is 100nm;
[0065] 4. SiH4, NH3 and N2O were introduced, and the gas flow ratio was controlled to be 1:5:7. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 200 s, and the discharge power was 12000 W to form a middle silicon oxynitride layer with a thickness of 20 nm.
[0066] 5. SiH4 and N2O were introduced, and the gas flow ratio was controlled to be 1:10. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 100 s, and the discharge power was 12000 W to form an upper silicon oxide layer with a thickness of 10 nm.
[0067] 6. Anneal the deposited silicon wafer at 500°C for 20 minutes to enhance the density and passivation effect of the composite layer.
[0068] 7. Back pressure, unloading from the boat to complete the process.
[0069] Example 5
[0070] A method for preparing a film layer resistant to ultraviolet attenuation of a solar cell, the method comprising:
[0071] 1. Place the passivated (passivation layer is an aluminum oxide layer with a thickness of 6nm) solar cells to be coated in a graphite boat;
[0072] 2. Place the graphite boat into the tubular coating reaction process furnace tube, heat and evacuate at the same time;
[0073] 3. Introduce NH3, SiH4 and TiCl4, control the gas flow ratio to NH3:SiH4:TiCl4=5:1:1, the deposition temperature is 500℃, the pressure is 500 Pa, the deposition time is 300s, the discharge power is 12000W, and the bottom SiN is formed. x: TiO2 composite layer (TiO2 doping weight percentage is 10%), the film thickness is 110nm;
[0074] 4. SiH4, NH3 and N2O were introduced, and the gas flow ratio was controlled to be 1:5:7. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 200 s, and the discharge power was 12000 W to form a middle silicon oxynitride layer with a thickness of 20 nm.
[0075] 5. SiH4 and N2O were introduced, and the gas flow ratio was controlled to be 1:10. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 100 s, and the discharge power was 12000 W to form an upper silicon oxide layer with a thickness of 10 nm.
[0076] 6. Anneal the deposited silicon wafer at 500°C for 20 minutes to enhance the density and passivation effect of the composite layer.
[0077] 7. Back pressure, unloading from the boat to complete the process.
[0078] Example 6
[0079] The method for preparing the anti-ultraviolet attenuation film layer of the solar cell provided in Example 6 is different from that in Example 1 in that the bottom layer is a TiO2 layer superimposed on the silicon nitride layer, and the remaining steps are the same as in Example 1. In this embodiment, the specific method for preparing the bottom layer includes:
[0080] First, SiH4 and NH3 were introduced, and the gas flow ratio was controlled to be 1:5. The deposition temperature was 475°C, the pressure was 200 Pa, the deposition time was 300s, and the discharge power was 12000W to form the bottom SiN x layer, thickness of 50 nm;
[0081] TiCl4 and N2O were then introduced, and the gas flow ratio was controlled to be 1:4. The deposition temperature was 475°C, the pressure was 200 Pa, the deposition time was 100s, and the discharge power was 10000W to form a TiO2 layer with a thickness of 10nm.
[0082] Example 7
[0083] The method for preparing the anti-ultraviolet attenuation film layer of the solar cell provided in Example 7 is different from that in Example 6 in that the lower layer is a silicon nitride layer superimposed on the TiO2 layer, and the thickness of the TiO2 layer is 10nm, SiN x The thickness of the layers is 50 nm; the TiO2 layer is on the side close to the cell, and the rest of the steps are the same as in Example 6. In this embodiment, the specific method of the bottom layer includes:
[0084] First, TiCl4 and N2O were introduced in a ratio of 1:4, with a deposition temperature of 475°C, a pressure of 200 Pa, a deposition time of 100 s, and a discharge power of 10,000 W to form a TiO2 layer with a thickness of 10 nm.
[0085] Then SiH4 and NH3 were introduced in a ratio of 1:5. The deposition temperature was 475°C, the pressure was 200 Pa, the deposition time was 300s, and the discharge power was 12000W to form a bottom SiNx layer with a thickness of 50nm.
[0086] Comparative Example 1
[0087] The method for preparing the anti-ultraviolet attenuation film layer of the solar cell provided in Comparative Example 1 is different from that in Example 1 in that the bottom layer is a silicon nitride layer, and the remaining steps are the same as those in Example 1. The specific method is as follows:
[0088] A method for preparing a film layer resistant to ultraviolet attenuation of a solar cell, the method comprising:
[0089] 1. Place the passivated cells to be coated in a graphite boat;
[0090] 2. Place the graphite boat into the tubular coating reaction process furnace tube, heat and evacuate at the same time;
[0091] 3. SiH4 and NH3 were introduced, and the gas flow ratio was controlled to be 5:1. The deposition temperature was 475°C, the pressure was 200 Pa, the deposition time was 300 s, and the discharge power was 12000 W to form an underlying silicon nitride oxide layer with a thickness of 60 nm.
[0092] 4. SiH4, NH3 and N2O were introduced, and the gas flow ratio was controlled to be 1:5:7. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 200 s, and the discharge power was 12000 W to form a middle silicon oxynitride layer with a thickness of 20 nm.
[0093] 5. SiH4 and N2O were introduced, and the gas flow ratio was controlled to be 1:10. The deposition temperature was 450°C, the pressure was 200 Pa, the deposition time was 100 s, and the discharge power was 12000 W to form an upper silicon oxide layer with a thickness of 10 nm.
[0094] 6. Anneal the deposited silicon wafer at 400°C for 20 minutes to enhance the density and passivation effect of the composite layer.
[0095] 7. Back pressure, unloading from the boat to complete the process.
[0096] The comparison of the film layer structures of Example 1 and Comparative Example 1 is shown in Table 1.
[0097] Table 1 Comparison of film structure between Example 1 and Comparative Example 1
[0098] film layer Comparative Example 1 Example 1 upper layer Silicon oxide Silicon oxide Middle level Silicon oxynitride Silicon oxynitride bottom layer Silicon nitride <![CDATA[Silicon nitride - TiO2]]>
[0099] Comparative Example 2
[0100] The method for preparing the anti-ultraviolet attenuation film layer of the solar cell provided in Comparative Example 2 is different from that in Example 1 in that the lower layer is a TiO2 layer, and the remaining steps are the same as those in Example 1.
[0101] The preparation method of the TiO2 layer comprises:
[0102] TiCl4 and N2O were introduced, the gas flow ratio was controlled to be 1:4, the deposition temperature was 475℃, the pressure was 200 Pa, the deposition time was 100s, the discharge power was 10000W, and a TiO2 layer with a thickness of 10nm was formed.
[0103] Comparative Example 3
[0104] The method for preparing the anti-ultraviolet attenuation film layer of the solar cell provided in Comparative Example 3 is different from that in Example 1 in that the middle layer is a titanium dioxide-doped silicon oxynitride layer, and the remaining steps are the same as in Example 1.
[0105] Specifically, the preparation method of the titanium dioxide-doped silicon oxynitride layer includes:
[0106] TiO2, SiH4, NH3 and N2O were introduced, and the gas flow ratio was controlled to be 1:1:5:7. The deposition temperature was 450℃, the pressure was 200Pa, the deposition time was 200s, and the discharge power was 12000W to form a middle titanium dioxide-doped silicon oxynitride layer with a thickness of 20nm.
[0107] Comparative Example 4
[0108] The method for preparing the anti-ultraviolet attenuation film layer of the solar cell provided in Comparative Example 4 is different from that in Example 1 in that the upper layer is a titanium dioxide-doped silicon oxide layer, and the remaining steps are the same as in Example 1.
[0109] Specifically, the preparation method of the titanium dioxide-doped aluminum oxide layer includes:
[0110] TiO2, SiH4 and N2O were introduced, the gas flow ratio was controlled to be 1:1:10, the deposition temperature was 450℃, the pressure was 200Pa, the deposition time was 100s, the discharge power was 12000W, and an upper silicon oxide layer was formed with a thickness of 10nm.
[0111] Performance testing:
[0112] By controlling the doping gas flow, the present invention achieves varying doping ratios of TiO2 in the lower layer. The specific doping ratios are determined through EDS (Energy-Dispersive X-ray Spectroscopy). The cell, with the UV-resistant film layer, is then subjected to conventional solar cell manufacturing processes, including Ag electrode printing, to complete the cell fabrication process. The performance of the resulting cell was then tested, with the results shown in Table 2.
[0113] Table 2 Test results
[0114]
[0115] Note: “-” in the table means that the item does not exist.
[0116] Table 2 compares the present invention's examples with the prior art. By controlling the gas flow rate, the bottom-layer doping ratios of 1%, 5%, 8%, 10%, and 15% were achieved. As shown in Table 2, the 8% doping ratio of the present invention achieves a 0.04% higher efficiency, 21mA higher Isc, and 1% lower UV60 attenuation than the BSL production line, achieving significant results that meet expectations. The 15% doping ratio also shows a 0.74% lower efficiency than the production line. This is primarily due to the fact that excessive TiO2 doping reduces the transmittance of the front-layer film, leading to a decrease in short-circuit current, which in turn affects efficiency.
[0117] Comparative Example 1 shows that when the bottom layer is undoped with TiO2, the absence of TiO2 to absorb UV light allows a large number of high-energy photons to penetrate the cell interior, resulting in significantly higher UV attenuation. Comparative Example 2 shows that when titanium dioxide alone is used in the bottom layer, the hydrogen source is reduced, resulting in a decrease in the overall film passivation performance and, consequently, in the cell performance.
[0118] Comparative Examples 3 and 4 show that since the refractive index of titanium dioxide is between 2.2 and 2.9, the refractive index of silicon oxide (SiO2) is approximately 1.45, the refractive index of silicon oxynitride is between 1.6 and 1.9, and the refractive index of silicon nitride (Si3N4) is approximately 2.0 to 2.1, when TiO2 is doped into the bottom layer, the three-layer film gradually transitions the refractive index of the incident light through a refractive index gradient from low to high (the refractive index close to the silicon substrate is high), thereby reducing reflection losses and optimizing the optical performance of the film layer, thereby improving the performance of the battery. When TiO2 is doped into the bottom layer, the refractive index gradient from low to high can be better achieved for the three-layer film, thereby improving the passivation performance of the entire film layer.
[0119] The technical features of the above-described embodiments can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0120] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be determined by the appended claims.
Claims
1. A film layer for resisting ultraviolet attenuation of a solar cell, characterized in that: include: On the upper surface of the crystalline silicon, there are three layers of anti-ultraviolet attenuation film, namely upper, middle and lower layers; the upper layer is a silicon oxide layer; The middle layer is a silicon oxynitride layer; The lower layer is a silicon nitride-TiO2 composite layer.
2. The anti-ultraviolet attenuation film layer of a solar cell according to claim 1, characterized in that: The silicon nitride-TiO2 composite layer includes: a silicon nitride layer and a TiO2 layer stacked together, or a TiO2-doped silicon nitride layer.
3. The anti-ultraviolet attenuation film layer of a solar cell according to claim 2, characterized in that: When the silicon nitride-TiO2 composite layer is a TiO2 layer superimposed on a silicon nitride layer, the thickness of the TiO2 layer is 5nm~20nm; Alternatively, when the silicon nitride-TiO 2 composite layer is a TiO 2 -doped silicon nitride layer, the weight percentage of TiO 2 doping in the TiO 2 -doped silicon nitride layer is 1% to 10%.
4. The anti-ultraviolet attenuation film layer of a solar cell according to claim 1, characterized in that: The thickness of the silicon nitride-TiO2 composite layer is 50nm~120nm.
5. The method for preparing the anti-ultraviolet attenuation film layer of a solar cell according to any one of claims 1 to 4, characterized in that: include: S1, depositing a silicon nitride-TiO2 composite layer on the cell to be coated as the lower layer of the anti-ultraviolet attenuation film layer; depositing a silicon oxynitride layer on the lower layer as the middle layer of the anti-ultraviolet attenuation film layer of the solar cell; and depositing a silicon oxide layer on the middle layer as the upper layer of the anti-ultraviolet attenuation film layer of the solar cell; S2, annealing the cell after the treatment in S1 to obtain the anti-ultraviolet attenuation film layer of the solar cell.
6. The preparation method according to claim 5, wherein In S1, the thickness of the lower layer is 50 nm to 120 nm.
7. The preparation method according to claim 5, wherein In S1, a silicon source, a nitrogen source, and a titanium source are introduced, and the ratio of the nitrogen source, the silicon source, and the titanium source is controlled to be 5-50:1-10:1 to deposit the lower layer.
8. The preparation method according to claim 7, wherein The deposition temperature of the lower layer is 300° C. to 500° C., the pressure is 100 Pa to 500 Pa, the deposition time is 150 s to 300 s, and the discharge power is 9000 W to 15000 W.
9. The preparation method according to claim 8, wherein In S2, the annealing conditions are: annealing temperature is 400°C to 500°C, and time is 10 min to 20 min.
10. A solar cell comprising the anti-ultraviolet attenuation film layer of the solar cell according to any one of claims 1 to 4 or comprising a film layer prepared by the preparation method according to any one of claims 5 to 9.
Citation Information
Patent Citations
Film layer structure for improving UV attenuation of TOPcon battery
CN119521856A
Crystalline silicon solar cell antireflection film
CN103000705A
Solar cell anti-reflection film and preparation method thereof
CN105097962A
Solar cell and preparation method thereof
CN119789602A
Double-layer antireflection film of crystalline silicon solar cell
CN202268353U